Equity research: Greenvolt - Renewable Energy, S.A. - Costa, Rui Pedro Amado (2023)
The objective of this Dissertation is to analyze and value Greenvolt – Renewable Energy S.A.’s stock, using the Discounted Cash-flow and Multiples methodologies, to obtain a fundamental price. The dissertation expands this by exploring the motives for the observed underpricing phenomena of the stock and analyzing the subsequent evolution of the share price based on external events and theories put forward by previous research. Underpricing, as well as its consequences, have been widely studied and many explanations for both have been put forward. In this Dissertation, several explanations for underpricing are tested. Two valuations of Greenvolt are presented: the first one is dated July 2021 (immediately preceding the Initial Public Offering) and the second one is dated May 2023. To end the analysis, statistical testing of the presence of information asymmetry surrounding Greenvolt stock shall give us an insight into the validity of Information Asymmetry-based explanations for underpricing. Greenvolt is a Portuguese firm operating in the renewable energy industry, positioned upstream in the value chain, and specializing in the development of renewable energy projects (also producing and selling electricity). As shown throughout the analyses conducted, I find that Greenvolt stock was undervalued both at the time of the Initial Public Offering (IPO) and as of May 2023. I also observe greater volatility from Greenvolt’s stock when compared to its peers, which is plausibly explained by the short lifespan of the firm, its innovative business model, and, as demonstrated in the Dissertation, the subsequent information asymmetry (IA) surrounding the firm.